Transformation of the Political Parties of the EU Member States - Tryma, Kateryna; Karaman, Kostiantyn; Parlyk, Vladislav; Svietlakova, Maria (International Journal of Criminology and Sociology, 2022)
The study aims to provide an analysis and systematize the complex of factors influencing the transformation of party systems. We attempt to identify the relationship between their general and specific influences in particular countries to explore the transformation process's general patterns and national characteristics in European Union's political spaceion. This study's method is based on an overview of the unique bibliography collected by the researchers, which includes sources devoted to the study of foreign parties and party systems in the European Union by modern political scientists. The analysis shows the specification of internal and external factors that influence the adaptation of the political parties and systems to the EU's changing situation, country, and society. The modern transformation of political parties and party systems in the EU is caused by the phenomenon of globalization, the financial and economic crisis of 2008-2009, the overlapping migration crisis of 2015-2026, Brexit and changes in the institutional environment, and the democratic deficit in the EU itself. The obtained results have verified the research hypothesis. This study discussed modern tendencies in the transformation of political parties and political space in the European Union under the influence of different, controversial but discrete factors of development and complete explanation about the essence of new types of political parties